2015
DOI: 10.1371/journal.pone.0143291
|View full text |Cite
|
Sign up to set email alerts
|

Polymicrobial Oral Infection with Four Periodontal Bacteria Orchestrates a Distinct Inflammatory Response and Atherosclerosis in ApoEnull Mice

Abstract: Periodontal disease (PD) develops from a synergy of complex subgingival oral microbiome, and is linked to systemic inflammatory atherosclerotic vascular disease (ASVD). To investigate how a polybacterial microbiome infection influences atherosclerotic plaque progression, we infected the oral cavity of ApoEnull mice with a polybacterial consortium of 4 well-characterized periodontal pathogens, Porphyromonas gingivalis, Treponema denticola, Tannerealla forsythia and Fusobacterium nucleatum, that have been identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
101
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(104 citation statements)
references
References 35 publications
3
101
0
Order By: Relevance
“…Previous studies, by increasing the effectiveness of treatment and ensuring the comfort of the patient [6,37,38]. The results of this pilot study require confirmation based on trials in larger groups of patients.…”
Section: Discussionmentioning
confidence: 81%
“…Previous studies, by increasing the effectiveness of treatment and ensuring the comfort of the patient [6,37,38]. The results of this pilot study require confirmation based on trials in larger groups of patients.…”
Section: Discussionmentioning
confidence: 81%
“…This primary environmental risk factor (infection) has the potential for pathogenic interplay in the hetero/homozygous apoε4 genotype via initiation of an intrinsic cascade of risk factors (infection>inflammation) for dyslipidaemia. Another common feature of all the mono and polyinfected experiments in ApoE −/− mice [71,75] was the abundant expression of NPY gene in vascular tissues [75]. This suggests an intricate relationship of NPY gene and chronic infections with possible manifestation for the development of insulin resistance as discussed below.…”
Section: Periodontal Disease In Apoe −/− Micementioning
confidence: 91%
“…Nevertheless, there is a suggestion of an emerging role of NPY gene that may be of relevance to this metabolic syndrome via its effect on the HPA activity as demonstrated by ApoE −/− mice following an oral infection [75].…”
Section: Type 2 Diabetes Mellitusmentioning
confidence: 99%
“…These invaders are often ineffective WH colonisers (or less virulent) unless they are together with other specific taxa. For instance, to test the hypothesis that periodontitis (gum disease) is caused by a disbiotic microbial community, mice were infected with four different bacteria species simultaneously and compared them to mono-infections (Chukkapalli et al 2015). They found that polymicrobial infections were more virulent, formed plaques more readily and altered immunity functioning.…”
Section: Single and Poly-microbial Invasionsmentioning
confidence: 99%